The gathering - Enright, Anne 1962- (New York Black Cat, 2007)
As nine members of the Hegarty clan gather for the wake of their drowned brother Liam, his sister Veronica remembers the secret he shared with her about what happened in their grandmother's house thirty years ago, a betrayal that spans three generations.
The nine surviving children of the Hegarty clan are gathering in Dublin for the wake of their wayward brother, Liam, drowned in the sea. His sister, Veronica, collects the body and keeps the dead man company, guarding the secret she shares with him - something that happened in their grandmother's house in the winter of 1968. As Enright traces the line of betrayal and redemption through three generations, she shows how memories warp and secrets fester.--BOOK JACKET.
Man Booker Prize for Fiction, 2007.
Keywords: Family secrets -- Fiction; Families -- Ireland -- Fiction; Dublin (Ireland) -- Social life and customs -- Fiction